Second primary neoplasms in patients with lung and gastroenteropancreatic neuroendocrine neoplasms: Data from a retrospective multi-centric study. Issue 3 (March 2021) - Massironi, S.; Campana, D.; Pusceddu, S.; Albertelli, M.; Faggiano, A.; Panzuto, F.; Smiroldo, V.; Andreasi, V.; Rossi, R.E.; Maggio, I.; Torchio, M.; Dotto, A.; et al.
Abstract: Background: Patients with sporadic neuroendocrine neoplasms may exhibit a higher risk of a second primary tumor than the general population. Aim: This study aimed to analyze the occurrence of second primary malignancies. Methods: A retrospective cohort of 2757 patients with sporadic lung and gastro-entero-pancreatic neuroendocrine neoplasms, managed at eight Italian tertiary referral Centers, was included. Results: Between 2000 and 2019, a second primary malignancy was observed in 271 (9.8%) neuroendocrine neoplasms patients with 32 developing a third tumor. There were 135 (49.8%) females and the median age was 64 years. The most frequent locations of the second tumors were breast (18.8%), prostate (12.5%), colon (9.6%), blood tumors (8.5%), and lung (7.7%). The second primary tumor was synchronous in 19.2% of cases, metachronous in 43.2%, and previous in 37.6%. As concerned the neuroendocrine neoplasms, the 5- and 10-year survival rates were 87.8% and 74.4%, respectively. PFS for patients with a second primary malignancy was shorter than for patients without a second primary malignancy. Death was mainly related to neuroendocrine neoplasms. Conclusion: In NEN patients the prevalence of second primary malignancies was not negligible, suggesting a possible neoplastic susceptibility. Overall survival was not affected by the occurrence of a second primary malignancy.